Clinico-Pathological Correlations of the Most Common Neurodegenerative Dementias - Taipa, Ricardo; Pinho, João; Melo-Pires, Manuel (Frontiers in Neurology, 2012)
Neurodegenerative dementias are a group of neurological disorders characterized by deterioration in several cognitive domains in which there is selective and progressive loss of specific populations of neurons. The precise neurobiological basis for the different neurodegenerative dementias remains unknown. Nevertheless, in the most common neurodegenerative disorders there are biochemical changes in a specific protein that often promotes their deposition. Over the last decade, many researchers have investigated the neuropathological background of the phenotypic variability in neurodegenerative dementia and identified a wide spectrum of associations between clinical syndromes and molecular pathologies. The next decades promise treatments that are directed at changing pathogenesis, increasing clinician’s awareness of the full clinical spectrum under the umbrella of the same molecular pathology. The purpose of this brief review is to describe the key neuropathological features of the most common neurodegenerative dementias and the relationship with the clinical syndromes described in clinicopathological studies.